Chronic Physical Activity for Attention Deficit Hyperactivity Disorder and/or Autism Spectrum Disorder in Children: A Meta-Analysis of Randomized Controlled Trials - Zhang, Meiqi; Liu, Zhan; Ma, Hongtao; Smith, Daniel M. (Frontiers in Behavioral Neuroscience, 2020)
Purpose: To explore the effects of physical activity (PA) intervention on executive function (EF) and motor skills (MS) among children with attention deficit hyperactivity disorder and/or autism spectrum disorder (ASD). Methods: Relevant studies were sourced from PubMed, Web of Science, EMBASE, Cochrane Library, CNKI and Wanfang Data. Only randomized controlled trials (RCT) were included based upon the following criteria: (1) participants were children and clinically diagnosed with ADHD/ASD, (2) intervention strategies were identified as chronic physical activity, and (3) EF (e.g., cognitive flexibility) and/or MS (e.g., gross motor skills) were measured at baseline and post-intervention and compared with an eligible control group. Results: Eleven studies involving 346 participants were finally identified. PA elicited significant improvements in EF and MS in children with ADHD/ASD. Regarding changes in the EF of participants, PA showed a great improvement in overall EF [standardized mean difference (SMD): 0.90, 95% confidence interval (CI) 0.49–1.30, p < 0.00001], inhibitory control (SMD: 1.30, 95% CI 0.58–2.02, p = 0.0004) and cognitive flexibility (SMD: 0.85, 95% CI 0.42–1.29, p = 0.0001), but no significant improvement in working memory (SMD: 0.28, 95% CI −0.15–0.71, p = 0.20). Significant improvements were also found with respect to gross motor skills (SMD: 0.80, 95% CI 0.30–1.30, p = 0.002), but no significant changes were found in fine motor skills (SMD: 0.30, 95% CI −0.91–1.52, p = 0.62). Conclusion: Chronic PA interventions may promote EF and MS in children with ADHD/ASD, especially in inhibitory control, cognitive flexibility, and gross motor skills. However, PA interventions seemed to have insignificant effects on working memory and fine motor skills to children with ADHD/ASD. PROSPERO registration number: CRD42019118622